Problematika Pertunjukan Wayang Kulit Dalam Prespektif Islam Analisis Pada Aspek Akidah, Ibadah, Muamalh - Taraman, Zahra; Azizah, Zahwa Fadiya; Aqilah, Syahla Haya; Amatullah, Hasna (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
Wayang Kulit is one of Indonesia’s cultural heritages that has existed since around ±1500 BC, functioning as a medium for entertainment, education, and the transmission of moral teachings. Originating from Hindu Indian traditions, Wayang Kulit later adapted and developed within the local Javanese cultural context. With the arrival of Islam, the Wali Songo—particularly Sunan Kalijaga—utilized Wayang Kulit as a medium of cultural da’wah by integrating Islamic values while maintaining existing cultural elements. This study aims to analyze the problematics of Wayang Kulit performances from an Islamic perspective, focusing on the aspects of aqidah (faith), ibadah (worship), and muamalah (social and ethical interactions). Using a qualitative descriptive and theological-normative approach, the research identifies several practices in Wayang Kulit that remain inconsistent with Islamic teachings, including beliefs in spiritual entities within the puppets, the use of offerings (sesajen), and prayers directed to beings other than Allah. The findings also reveal muamalah issues arising from commercialization and entertainment elements, such as inappropriate jokes and the shift of wayang from a medium of da’wah to predominantly entertainment-centered performances. The novelty of this study lies in its integrative analysis combining cultural interpretation with normative Islamic principles to assess the conformity of Wayang Kulit practices with the foundations of tauhid. The study concludes that while Wayang Kulit is an important cultural heritage, its preservation must align with Islamic values, ensuring that acts of worship remain solely directed to Allah and that moral and da’wah principles continue to guide the performance practices.